2016
DOI: 10.4314/ecajs.v21i1.139037
|View full text |Cite
|
Sign up to set email alerts
|

Evisceration of small bowel from umbilical vein catheterization in a preterm African neonate: An uncommon complication

Abstract: The umbilical vein helps in delivery of oxygen to the fetus in utero. It can be catheterized in the neonate for delivery of fluids and medications. Exchange blood transfusion is one common reason for umbilical vein catheterization. The procedure comes with its own complications. We report an uncommon complication; evisceration of the small bowel which was seen in an African neonate following umbilical vein catheterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…One study from Edo State Nigeria also reported intestinal evisceration through the umbilicus following an attempt at umbilical vein catheterization [3]. The author reported that the attempt at umbilical cannulation was difficult and an attempt was made to scrap and probe the umbilical region which may have caused the bowel evisceration [3]. Pathologies in the neonatal umbilical area may have also predisposed to bowel evisceration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study from Edo State Nigeria also reported intestinal evisceration through the umbilicus following an attempt at umbilical vein catheterization [3]. The author reported that the attempt at umbilical cannulation was difficult and an attempt was made to scrap and probe the umbilical region which may have caused the bowel evisceration [3]. Pathologies in the neonatal umbilical area may have also predisposed to bowel evisceration.…”
Section: Discussionmentioning
confidence: 99%
“…It provides a fast central venous access [2]. One of the most common indications for umbilical vein catheterization in neonates is for exchange blood transfusion in severely jaundiced babies [3]. However, umbilical catheterization is not without complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation